Village Financial Management: Based on Local Tradition - Khairul Shaleh; Hesty Juni Tambuati Subing; Andi Ina Yustina (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
This study aims to formulate village financial management based on local traditions of village communities. The research method uses a qualitative descriptive approach, which is a method that seeks to present a picture of the objective reality that occurs in a condition or environment in a particular place. Environmental context (Site) in this study is Sindang Pakuon Village, Cimanggung District, Sumedang Regency and Ciburial Village, Cimenyan District, Bandung Regency, West Java Province. Presence of village funds is acknowledged to have changed the face of the village which previously seemed neglected, now looks better. Village infrastructure such as village roads is more convenient for motorists and pedestrians. Road to distribution of agricultural products has been built so that the travel time to move agricultural products from the fields to the market location is faster. Although village funds have brought changes to public facilities in the countryside, they have a fading effect on aspects of village tradition. Emergence of this fading is because the nomenclature that regulates the use of village funds does not yet accommodate the local aspects of rural areas.